Dampak Pembangunan Modern Terhadap Keberadaan Situs Buni - Abudrrahim, Husein; Wardi, I Nyoman; ., Zuraidah (Humanis; Vol 24 No 2 (2020)DO - 10.24843/JH.2020.v24.i02.p14, 2020)
Buni site is one of the prehistoric relics in Bekasi Regency which has an important role for the development of history in the northern part of Java Island.There are several potential archeological remains at the Buni Site in the form of metal artifacts, stone axes, gold jewelery, beads, earthenware and conch shells. The existence of modern development around the Buni Site makes the Buni Site threatened its preservation. There are two modern developments flanking the Buni Site, which is a ship factory managed by PT. Tesco Indomaritim and PLTU (Steam Power Plant) managed by PT. Cikarang Listrikindo. This study aims to address the formulation of the problem the impact of modern development on the existence of the Buni Site and conservation efforts at the Buni Site. This study use the Archeology Resource Management theory. Data collection methods used were observation, literature study, and interviews. Data analysis techniques used ware qualitative and SWOT. There are two impacts given by modern development on the Buni Site. First, the damage and lost of the Buni site, the lost of the site area has made the Buni site narrow and lost the findings that have the potential to be left behind in the area of ??the ship factory and the power plant. Secondly, Muara Bakti Village, where Buni Site is located, is no longer known by the wider community as the Archaeological Site. Buni site is currently not used as a cultural heritage site, which can affect its preservation. Development of the Buni Site area as a tourist attraction, in the form of the Buni Cultural Museum can help preserve the Buni Site from damage.